Pengembangan Kebijakan Manajemen Bencana Berbasis Komunitas Studi Kasus di Kawasan Rentan Bencana - Rofika, Rofika; Saepudin, Eli Apud; Aulia, Linda; Merlita, Nahara; Talitha, Tasya Adela; Aqila, Azzahra Nayla (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
To reduce the likelihood of disasters occurring in vulnerable areas, an important approach used is community-based disaster management. The purpose of this research is to evaluate the development of community-based disaster management policies and find factors that influence how effectively they are implemented. Data was collected through participatory observation, in-depth interviews, and documentation studies through a qualitative descriptive approach. To ensure that the research results are valid, purposive sampling was used to select research informants. The informants included community leaders, disaster response volunteers, local community members, and local government representatives. Data analysis was conducted using triangulation techniques. The study showed that three main factors determine the success of community-based disaster management: (1) the level of community participation and empowerment in program planning and implementation, (2) the synergy between local wisdom and modern disaster management systems, and (3) policy and institutional support from the local government. Limited resources, coordination among stakeholders, and program sustainability are some of the issues faced. To achieve efficient and sustainable disaster management, this study suggests community capacity building, improved coordination between various parties, and policy making that is appropriate to the local context.